Count me in! including learners with special needs in mathematics classrooms - Storeygard, Judith (Corwin, 2016)
Between the pressure to meet standards and the overwhelming number of different learning needs that students have, planning lessons has become more complex. Judith Storeygard provides proven approaches to understanding the behaviors of children with special needs and effectively teaching all students. Using research-based and field-tested methodology, this book's teaching strategies include differentiated instruction, with an emphasis on co-teaching between general educators and special educators